Synthesis of pyrimido[4′, 5′:5, 6][1, 4]dithiepino[2, 3-b]quinoxalines: Derivatives of a novel seven membered ring system. (3rd April 2017) - Firoozi, Neda; Bakavoli, Mehdi; Eshghi, Hossein; Ramazanian, Navid; Akbarzadeh, Marziyeh
GRAPHICAL ABSTRACT: ABSTRACT: A convenient and efficient procedure for the synthesis of tetracyclic dithiepin derivatives is described through the condensation reaction of 2, 4-dichloro-5-(chloromethyl)-6- methylpyrimidine and quinoxaline-2, 3-dithiol followed by treatment with secondary amines.